Terms of Trade, Foreign Direct Investment, and Development: A Case of Intra-Asian "Kicking Away the Ladder"? - Konstantin M. Wacker; Philipp Großkurth; Tabea Lakemann (Asian Development Bank (ADB), 2014)
In this paper, we address in more detail the question raised in Wacker (2011b): why does foreign direct investment (FDI) generally have a positive impact on developing countries' terms of trade except in the case of South Asia? After arguing that such a negative relationship is generally detrimental for a country's growth strategy in a globalized context, we present some stylized facts about the Asian development experiences and the theoretical and empirical background for our question concerning the relationship of FDI and terms of trade in the development context. From here, we argue that South and East Asia have largely pursued different world market integration strategies that have been fostered by different types of FDI: While horizontally motivated FDI has helped East Asia achieve some market power in certain higher-value product niches, late-coming South Asian economies have successfully operated in global industries via price competitiveness, fueled by vertically motivated FDI. Different endowments in human capital provided a breeding ground for these differing development experiences. Our evidence suggests that latecomers in international markets cannot simply follow the same pathway to development as more advanced countries, but rather they must employ adapted alternatives. In addition, globalization might perpetuate traditional North–South patterns in increasing South–South interactions.
hdl:11540/1981
Keywords: F23; O11; O57; 330; Foreign direct investment (FDI); terms of trade; development; Prebisch–Singer hypothesis